Antihyperlipidemic, hepatoprotective and nephroprotective effects functional beverages containing soybean (Glycine max L.), sweet potato leaves (Ipomoea batatas L.), and red yeast rice on a high fat diet rats - Mahfudh, Nurkhasanah; Sari, Atika Orchida; Ikhtiari, Iradatul; Sulistyani, Nanik; Kumalasari, Ika Dyah; Othman, Fezah (Biome Scientia, 2024)
One of the primary risk factors for hyperlipidemia is an excessively high-fat diet. Due to their phytochemical composition and biological activity, red yeast rice (RYR), sweet potato (Ipomoea batatas L.) leaves and soybeans (Glycine max L.) are known to possess antihyperlipidemia and antioxidants effects. The purpose of this study is to ascertain how beverages containing soybeans, sweet potato leaves, and red yeast rice affect rats fed a high-fat diet in terms of hyperlipidemia, liver damage, and kidney damage. Five groups of rats were used: normal control, positive control using Commercial Smoothie Drink 1 (CSD1), 3.6 ml/day, negative control, and treatment groups receiving beverage doses of 1250 mg/kg and 2500 mg/kg respectively. Following the induction of the high-fat diet in the animals, functional beverage treatment was administered for 14 days starting on day 15 for a total of 28 days. The findings demonstrated that in rats fed a high-fat diet, the administration of functional beverages at a dose of 2500 mg/kg significantly (p<0.05) decreased serum levels of cholesterol, triglyceride, creatinine, blood urea nitrogen, serum glutamic pyruvic transaminase (SGPT) and serum glutamic oxaloacetic transaminase (SGOT). It is concluded that functional beverages may offer protection against hyperlipidemia, liver, and kidney damage caused by a high-fat diet.